Lysine-specific demethylase 1 induced epithelial–mesenchymal transition and promoted renal fibrosis through Jagged-1/Notch signaling pathway. (December 2021) - Zhang, Huali; Xing, Jiaming; Zhao, Lingwei
Objective: TGF-β1-induced excessive deposition of extracellular matrix (ECM) and epithelial-mesenchymal transition (EMT) process of tubular epithelial cells play critical roles in the progression of renal fibrosis. We are aimed to explore the effects of lysine-specific demethylase 1 (LSD1) in TGF-β1-treated HK-2 cells and in rats with unilateral ureteral obstruction (UUO), and to investigate the underlying molecular mechanism. Methods: TGF-β1-treated HK-2 cells and UUO-treated rats were used to establish the model of renal fibrosis in vitro and in vivo, respectively. Protein expression of LSD1, E-cadherin, a-smooth muscle actin (a-SMA), Vimentin, Jagged-1, Notch-1 and Notch-2 were detected by Western blot. The concentrations of type I collagen (Col-I) and Fibronectin (FN) were measured by ELISA. Transwell assay were used to assess cell invasion. Results: LSD1 was dramatically increased in TGF-β1-stimulated HK-2 cells. Knockdown of LSD1 decreased the TGF-β1-induced secretion of Col-I and FN, and suppressed TGF-β1-induced expression of E-cadherin, α-SMA and Vimentin, while suppressed cell invasion. Consistent with the in vitro data, the severe histopathological damage, collagen deposition and reduced E-cadherin, increased α-SMA induced by UUO was abated by the knockdown of LSD1 in vivo. Moreover, knockdown of LSD1 suppressed TGF-β1-induced expression of Jagged-1, Notch-1 and Notch-2. Furthermore, we found that inhibition of Notch signaling by a γ-secretase inhibitor RO4929097 almost recapitulated the effects of LSD1 knockdown in TGF-β1-induced HK-2 cells, and at least in part reversed the effects of LSD1 overexpression on EMT and ECM deposition in HK-2 cells. Conclusions: Taken together, LSD1 significantly impact on the progression of TGF-β1-mediated EMT and ECM deposition in HK-2 cells, and it may represent novel target for the prevention strategies of renal fibrosis.